Juridical Analysis of Liability for Compensation by Business Actors for Default Actions as an Effort to Protect Consumers - Saly, Jeane Neltje; Cahyadi, Silvia; Joshua, Mishael; Immanuel S, Maurend Benaya (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
According to Article 1 of Law Number 8 of 1999 concerning Consumer Protection, consumers are defined as individuals who use goods and services available in society for personal, family, other people or other living things, not for trading. Consumer protection involves aspects of legal protection provided to consumers to avoid losses that may arise as a result of using goods and services. Therefore, consumer protection laws regulate how consumer rights are protected and how these regulations are enforced through state administrative law, criminal law, and civil law, so that consumer rights are fulfilled and goods and services received from business actors can be fully protected. The responsibility of business actors for consumer losses is to provide compensation for damage, pollution or losses suffered by consumers due to the use of goods and services produced or traded by these business actors.